CATCH COMPOSITION AND SOME BIOLOGICAL ASPECTS OF SHARKS IN WESTERN SUMATERA WATERS OF INDONESIA - Dharmadi Dharmadi; Mahiswara Mahiswara; Kamaluddin Kasim (Indonesian Fisheries Research Journal, 2016)
This study was conducted in western Sumatera and since October 2013 to June 2014. The sampling locations in Banda Aceh and Sibolga-North Sumatera which were the largest base of fisheries in western Sumatera region. Shark landing recorded by enumerators was used  as sampling data daily . This research aim to describ sex ratio, size composition, catch composition of sharks, and length at first maturity. In Banda Aceh, the sharks as target fish collected by  sorting the bycatch from tuna longlines and tuna handlines. In Sibolga, sharks  is bycatch from fish net, bottom gillnet and purse seine. Overall, there were 20 species of shark caught in west Indian Ocean and landed at those fish landing sites, dominated by Spot tail shark (23%) and Silky shark (13%), whereas Hammerhead shark contributed about 10% and  Oceanic whitetip shark was only less than 1%. Almost of Spot tail shark, Silky shark, and Scalloped hammerhead that caught in that area were  immature, while for the almost part of Tiger shark and Pelagic thresher were  matured. The sex ratios for Spot tail shark, Silky shark, Tiger shark, Pelagic thresher, and Scalloped hammerhead caught and landed at Lampulo and Sibolga fish landing sites were not balance. The length at first maturity for Spot tail shark was Lm=87,1 cm and Lm = 213,2 cm total length for Tiger shark.